Вероятностное определение числа поражений молнией наземных объектов стержневого типа - Петков, Александр Александрович (НТУ "ХПИ", 2018)
В работе показано, что существующая методика определения числа поражений наземных объектов стержневого типа, которая представлена в нормативных документах по молниезащите, требует корректировки. Предложена многошаговая модель поражения наземного стержневого объекта, позволяющая определить вероятность поражения стержня в зависимости от расстояния между осями стержня и высоковольтного электрода. Получены данные для определения функции распределения вероятности поражения стержневого объекта при отношении высоты расположения высоковольтного электрода к высоте стержневого объекта равном H / h = 10 и H / h = 20. Материалы работы могут быть использованы для дальнейших исследований поражения длинной искрой различных объектов, расположенных на плоской поверхности.

Improvement of the procedure for determining the expected number of lightning lesions of rod-type objects in the probabilistic formulation of the problem. Methodology. Mathematical modeling of the probability of affection of a rod object located on the surface of a ground, using a multi-step model of motion of a long spark, the variational coefficients of which are determined from the results of physical experiments. Description of data by methods of probability theory and mathematical statistics. Results. The probability distribution functions of the impact of the core object are determined. It is shown that the existing norms for determining the lightning capture zone give an underestimate. Originality. The method of determining the zone of capture of lightning by objects of the rod type has been further developed. Practical value. Based on the calculations carried out, it is proposed to correct the existing regulatory documents on the protection of buildings and structures against direct lightning
Probabilistic determination of the number of lightning defeat in ground-based rod-type objects
Keywords: математическая модель; вероятность поражения; доверительный интервал; функция распределения; стержневой объект; mathematical model; probability of defeat; confidence interval; distribution function; core object